2014
DOI: 10.4103/0255-0857.129801
|View full text |Cite
|
Sign up to set email alerts
|

Same day sputum smear microscopy approach with modified ZN staining for the diagnosis of pulmonary tuberculosis in a microscopy centre at Rajahmundry

Abstract: Diagnosis of lung tuberculosis is possible with two spot sputum samples with modified ZN staining.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 5 publications
2
25
1
Order By: Relevance
“…In the current study, near to 3% of morning sputum microscopy results had incremental yields from the two spot (SS) sample, which was higher than 0.0% (no) incremental yields reported in South Western Uganda, 0.29% reported in India and 0.37% reported Rajahmundry India [9,11,12]. The incremental yield difference among serials of sputum samples might be related to many factors including: Instruction given to patients to submit quality and adequacy of sputum samples, time of sputum collection (the bacillary load increase in sputum spout out in the early morning), patient understanding how to collect quality of sputum samples and professional exercise on the way to guide and explain the quality of sputum submit for diagnosis and testing performed on good quality of sputum may impacts on yield of sputum microscopy diagnostic.…”
Section: Discussioncontrasting
confidence: 74%
“…In the current study, near to 3% of morning sputum microscopy results had incremental yields from the two spot (SS) sample, which was higher than 0.0% (no) incremental yields reported in South Western Uganda, 0.29% reported in India and 0.37% reported Rajahmundry India [9,11,12]. The incremental yield difference among serials of sputum samples might be related to many factors including: Instruction given to patients to submit quality and adequacy of sputum samples, time of sputum collection (the bacillary load increase in sputum spout out in the early morning), patient understanding how to collect quality of sputum samples and professional exercise on the way to guide and explain the quality of sputum submit for diagnosis and testing performed on good quality of sputum may impacts on yield of sputum microscopy diagnostic.…”
Section: Discussioncontrasting
confidence: 74%
“…Most of the studies conducted hitherto have been under trial conditions and there is a lack of evidence from routine programme settings [710] and limited, conflicting information from India. A study from South India showed that same day microscopy was as effective as the conventional strategy [11]; whereas another study from North India showed that same day microscopy missed a considerable number of smear positive TB patients [12]. Both the studies were conducted in tertiary care hospitals with a limited sample size and were not representative of routine programme conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Inspite of the availability of various techniques such as culture, molecular techniques, serodiagnostic methods, in this study, ZN staining was used to stain the sputum smears. LED fluorescent staining is a rapid, sensitive technique compared to ZN technique [1,2,11]. But by considering the advantages such as rapidity, ease in the technique, ZN staining was used in the current study to stain the sputum smears.…”
Section: Resultsmentioning
confidence: 99%